Performance of Agri - Warehousing in Maharashtra and Market Potential for Negotiable Warehouse Receipts Finance in India - Rangasamy, N. (Indian Journal of Marketing, 2013)
The present study has critically analyzed the economic performance of Maharashtra State Warehousing Corporation by using the tabular analysis method. The study found that net profit before tax had continuously increased from ₹ 1754.20 lakhs to ₹ 3526.03 lakhs (50.24% increase) during the last six years (2005-2010). The capacity utilization percent ranged between 74 to 79%. The financial analysis ratios, that is, gross profit to turnover was 32.63%, net profit to total turnover (27.99 %) and net profit after tax to total turnover (18.46%) were positive, return on capital employed was 10.32%, and current ratio was 1.42: 1. All these economic performance indicators and financial ratios highlight the incredible economic performance and positive growth of agri- warehousing in Maharashtra. On the other hand, the warehouses are still facing a lot of constraints in their warehousing operations . The market potential for warehouse receipt financing in India was estimated at ₹ 19000 crore, and also, negotiable warehouse receipt financing is facing quite a few challenges in India. Hence, the present study has suggested that training and awareness programs should be conducted for farmers, warehouse managers, and support staff; modern warehouses are the need of the hour; warehouses should complete accreditation, registration, and certification; high margins and stamp duty on warehouse receipt finance may be reduced for farmers and other depositors. Also, additional 35 million MT storage capacity may be created at the all India level by promoting private sector participation through various public - private partnership measures.